Experimental infections in red-legged partridges reveal differences in host competence between West Nile and Usutu virus strains from Southern Spain - Llorente, Francisco; Gutiérrez-López, Rafael; Pérez-Ramirez, Elisa; Sánchez-Seco, María Paz; Herrero, Laura; Jiménez-Clavero, Miguel Ángel; Vázquez, Ana (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction West Nile virus (WNV) and Usutu virus (USUV) are emerging zoonotic arboviruses sharing the same life cycle with mosquitoes as vectors and wild birds as reservoir hosts. The main objective of this study was to characterize the pathogenicity and course of infection of two viral strains (WNV/08 and USUV/09) co-circulating in Southern Spain in a natural host, the red-legged partridge (Alectoris rufa), and to compare the results with those obtained with the reference strain WNV/NY99. Methods WNV inoculated birds were monitored for clinical and analytical parameters (viral load, viremia, and antibodies) for 15 days post-inoculation. Results and discussion Partridges inoculated with WNV/NY99 and WNV/08 strains showed clinical signs such as weight loss, ruffled feathers, and lethargy, which were not observed in USUV/09-inoculated individuals. Although statistically significant differences in mortality were not observed, partridges inoculated with WNV strains developed significantly higher viremia and viral loads in blood than those inoculated with USUV. In addition, the viral genome was detected in organs and feathers of WNV-inoculated partridges, while it was almost undetectable in USUV-inoculated ones. These experimental results indicate that red-legged partridges are susceptible to the assayed Spanish WNV with pathogenicity similar to that observed for the prototype WNV/NY99 strain. By contrast, the USUV/09 strain was not pathogenic for this bird species and elicited extremely low viremia levels, demonstrating that red-legged partridges are not a competent host for the transmission of this USUV strain.